An Efficient Synthesis of Dopamine Transporter Tracer [(18)F]FECNT - Murali, D. (2012)
A simple synthesis of the dopamine transporter ligand [(18)F]FECNT with high radiochemical yield and short synthesis time, suitable for routine production is reported. Reaction of 2β-carbomethoxy-3β-(4-chlorophenyl)nortropane with [(18)F]2-fluoroethyl triflate ([(18)F]FEtOTf) at room temperature for 4 min. provided [(18)F]FECNT in 84% decay corrected radiochemical yield. Since [(18)F]FEtOTf was prepared from [(18)F]2-fluoroethyl bromide that was isolated from its starting material, formation of unwanted side products and the amount of expensive precursor used could be greatly reduced. The overall radiochemical yields of [(18)F]FECNT were 40% (n=29) and the total synthesis time was ca. 100 min. The average specific activity of [(18)F]FECNT was 377.4 GBq/µmol (10.2 Ci/µmol).